Mergers and alliances the operational view and cases - Woodsworth, Anne; Penniman, William David, 1937- (Emerald, 2013)
Volume 37 of Advances in librarianship presents detailed examples of local and regional mergers and collaborations and serves as a companion to Volume 36 which presented a comprehensive broad review of the factors that lead to mergers and other alliances, and the methods used to ensure effective and successful collaborations. While corporate mergers make headlines, library and information science examples, especially at regional an local levels, have less visibility. This volume demonstrates that such efforts are occurring in libraries, among LIS degree programs, and enterprises including networks and consortia. They are occurring as economic conditions around the world mandate consolidation and/or collaboration among agencies and enterprises to reduce or curtail expenditures.
Includes index.
Keywords: Libraries -- Mergers.; elektronické knihy; electronic books